2015
DOI: 10.1002/dneu.22327
|View full text |Cite
|
Sign up to set email alerts
|

Zebrafish TARP Cacng2 is required for the expression and normal development of AMPA receptors at excitatory synapses

Abstract: Fast excitatory synaptic transmission in the CNS is mediated by the neurotransmitter glutamate, binding to and activating AMPA receptors (AMPARs). AMPARs are known to interact with auxiliary proteins that modulate their behavior. One such family of proteins is the transmembrane AMPA receptor-related proteins, known as TARPs. Little is known about the role of TARPs during development, or about their function in non-mammalian organisms. Here we report the presence of TARPs, specifically the prototypical TARP, st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…Interestingly Nptn, a critical protein for long‐term potentiation at Hp excitatory synapses, also linked to AD (Ilic et al, 2019 ), was downregulated in 3xTg‐AD ChN mice compared to NonTg ChN counterparts (Log 2 FC = −1.55), and Ch‐ downregulated this protein in both NonTg (Log2 FC = −2.13) and 3xTg‐AD mice (Log 2 FC = −3.44). Moreover, proteins that modulate AMPA receptors Cacng8 (Log 2 FC = −1.00), Lrrtm1 (Log 2 FC = −1.34), Frrs1l (Log 2 FC = −1.38), as well as NMDA receptors Grin2a (Log 2 FC = −1.49), Clstn1 (Log 2 FC = −1.05), were also downregulated by Ch‐ (Bhouri et al, 2018 ; Roy et al, 2016 ; Stewart et al, 2019 ), suggesting that Ch‐ can contribute to postsynaptic membrane dysfunction in AD. Previous work has shown that choline modulates the expression of alpha7 nicotinic acetylcholine and Sigma‐1 receptors (Velazquez et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly Nptn, a critical protein for long‐term potentiation at Hp excitatory synapses, also linked to AD (Ilic et al, 2019 ), was downregulated in 3xTg‐AD ChN mice compared to NonTg ChN counterparts (Log 2 FC = −1.55), and Ch‐ downregulated this protein in both NonTg (Log2 FC = −2.13) and 3xTg‐AD mice (Log 2 FC = −3.44). Moreover, proteins that modulate AMPA receptors Cacng8 (Log 2 FC = −1.00), Lrrtm1 (Log 2 FC = −1.34), Frrs1l (Log 2 FC = −1.38), as well as NMDA receptors Grin2a (Log 2 FC = −1.49), Clstn1 (Log 2 FC = −1.05), were also downregulated by Ch‐ (Bhouri et al, 2018 ; Roy et al, 2016 ; Stewart et al, 2019 ), suggesting that Ch‐ can contribute to postsynaptic membrane dysfunction in AD. Previous work has shown that choline modulates the expression of alpha7 nicotinic acetylcholine and Sigma‐1 receptors (Velazquez et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, we found that knockdown of zebrafish Stargazin γ-2a resulted in a reduction of AMPA mEPSC amplitude and frequency associated with Mauthner cells, and that the expression of AMPARs appeared to be reduced in embryonic brain [19]. To determine if knockdown of γ-4a or γ-4b had similar developmental effects on AMPA currents, we patch-clamp-recorded AMPA mEPSCs from M-cells of newly hatched embryos.…”
Section: Resultsmentioning
confidence: 99%
“…While TARPs have been extensively studied in mammals, there is very little known about their roles in nonmammalian vertebrates such as zebrafish. Our group was the first to present functional data on the role of the prototypical TARP γ-2, in developing zebrafish, and found it to be necessary for the trafficking of AMPAR to synaptic membranes [19], consistent with its roles in mammals. Few studies have focused on the role of other members of the type I family such as γ-4 or γ-8 in nonmammalian vertebrates.…”
Section: Introductionmentioning
confidence: 93%
“…; Henley and Wilkinson ) and changes in escape responses (smaller tail velocities and aberrant turning directions) (Roy et al . ). It has been demonstrated that AMPARs mediate synaptic transmission from cone photoreceptors to OFF bipolar cells in zebrafish (Wong et al .…”
Section: Discussionmentioning
confidence: 97%